Optimalisasi Produksi Pada UMKM Ayam Gepuk Pak Gembus Menggunakan Pendekatan Linear Programming dalam Perspektif Manajemen Operasional - Hidayat, Dwiky Fachrul; Rizqiansyah, Muhammad Aziz; Firmansyah, Muhammad Raditya; Syukron, Syukron (Universitas Pahlawan Tuanku Tambusai, 2025)
This study aims to optimize the production process at the Pak Gembus Chicken Gepuk UMKM in order to increase efficiency and business profits. The main problem faced is determining the right combination of production amidst limited resources. In operational management, production efficiency is a key factor in increasing the competitiveness and sustainability of small and medium-scale businesses. The research method used in this study combines the library study approach and field study. Library study is used to formulate a theoretical framework regarding operational management and linear programming. Meanwhile, field studies are conducted by collecting primary data in the form of production capacity, working hours, availability of raw materials, and profit margins for each product. The Linear Programming model is compiled and completed using QM for Windows software. The results of the study show that optimal production is achieved by stopping the production of Regular Chicken Gepuk and increasing the production of Jumbo and Special Chicken Gepuk. This strategy reduces the total number of production units by 11.1% but increases total profits by 24.3%. This conclusion shows that the Linear Programming approach is effective in data-based operational decision making in culinary UMKM.